Legislative reform viewed from the interrelations of certain criminal offences - Delić Nataša (Crimen (Beograd), 2025)
Denoting the negative trends within the reform of the special part of criminal law, this paper critically analyzes the following criminal offences: aggravated murder (art. 114, par. 1, it. 6, 7 and 8. CC), serious bodily harm (art. 121, par. 6. CC), obstruction of justice (art. 336b par. 2. CC), endangerment of safety (art. 138, par. 3. CC), and assault on a lawyer (art. 336v CC). Apart from introducing more severe penalties for a great number of criminal offences, the most important characteristic of the Criminal Code's special part reform is the accentuated criminalization, i.e. proscription of new criminal offences. Such tendencies of the legislator have had several negative consequences. First of all, the zone of incrimination has been widened, and special forms of existing criminal offences have been proscribed as separate incriminations. Furthermore, incriminations with undeterminable content and scope impair efficient application of law and undermine legal certainty. Finally, certain existing incriminations are not justified in the systematic context. All of the aforementioned trends have greatly endangered the principle of lex certa and are tendentiously transforming criminal law from ultima ratio, the ultimate mean of society's defence from unwanted acts and behaviours to prima ratio, which is incompatible with criminal law's nature and purpose.